Postcards from the Río Bravo Border : Picturing the Place, Placing the Picture, 1900s-1950s - Arreola, Daniel D. (Daniel David), 1950- (Book collections on Project MUSE., 2013)
Making use of an extensive archive of photo postcards, this historical geography traces the transformation of Mexican border towns into modern cities and destinations for American tourists in the twentieth century.